[Coast Near Eldfell] - Streng, Evelyn Fiedler (1975)
Photograph of the coast near Eldfell. The black, curved beach sits beside the light blue ocean and a brown, rocky hill. A green, rounded mountain is visible in the distance to the left. The sky is foggy and grey in the background.